Reformed and evolutionary epistemology and the noetic effects of sin - De Cruz, H; De Smedt, J (2013)
Despite their divergent metaphysical assumptions, Reformed and evolutionary epistemologists have converged on the notion of proper basicality. Where Reformed epistemologists appeal to God, who has designed the mind in such a way that it successfully aims at the truth, evolutionary epistemologists appeal to natural selection as a mechanism that favors truth-preserving cognitive capacities. This paper investigates whether Reformed and evolutionary epistemological accounts of theistic belief are compatible. We will argue that their chief incompatibility lies in the noetic effects of sin and what may be termed the noetic effects of evolution, systematic tendencies wherein human cognitive faculties go awry. We propose a reconceptualization of the noetic effects of sin to mitigate this tension. © 2012 Springer Science+Business Media B.V.